Design of WEB-Based Transportation Information System and Invoice Recapitulation at Chandra Lie Expedition - Angelica, Felicia; Pratama, Yovi; Amroni, Amroni (International Conference on Business Management and Accounting, 2024)
Chandra Lie Expedition is a truck rental company started by Chandra Lie in 2018 and used for shipping kernels, coal, palm oil, and shells. The address of this expedition is 36135, East Jambi District, Jalan Sentot Ali Basa Payo Agile. When admins want to report invoices, recapitulation of invoices previously recorded using the book technique, this often occurs errors in summing the total bill and entering the transaction date. The admin needs to use Microsoft Word to draft a road letter for the driver after creating an invoice recapitulation report. It will take some time. Owners and admins should meet daily to request invoice reports for the previous day. Data that is not connected to each other. The goal of the project is to develop a web-based design tool that will make it easier for actors to perform. The steps to be taken to solve this challenge include identification, information retrieval based on theoretical foundations, observation techniques, and analysis to identify solutions to the problems faced by the expedition. Devices and software serve as research tools and materials. The purpose of the conclusion of this study is to facilitate reporting and summary of invoice reports.